Unexpected diversification of DENV2 genotype III in Colombia: New Insights and application of the globalized nomenclature - Eliana P. Calvo; Leidy Johana Madroñero; Lenny Marcela Hernández; Jhann Andrés Arturo; Hernando Pinzón; Félix Giovanni Delgado; Myriam Lucia Velandia-Romero; Verity Hill; Nathan D. Grubaugh; Jaime Eduardo Castellanos (PLoS ONE, 2026)
Dengue is the most prevalent mosquito-borne viral disease worldwide and constitutes a major public health concern in Colombia. The disease is caused by four antigenically distinct dengue virus serotypes (DENV-1 to DENV-4), which share more than 65% genome identity. Although all four serotypes co-circulate in Colombia, secondary infections with DENV-2 have frequently been associated with more severe clinical outcomes. DENV-2 comprises six genotypes, of which genotype III has been the dominant lineage in the Americas over the past two decades. In this study, we investigated the evolutionary dynamics of DENV-2 genotype III in Colombia by analyzing available whole-genome coding sequences together with twenty-six newly generated genomes. Bayesian and maximum-likelihood phylogenetic approaches were applied to infer evolutionary relationships and temporal patterns. To harmonize lineage definitions and facilitate regional comparisons, we adopted the recently proposed hierarchical lineage nomenclature and used the Genome Detective Dengue typing tool for automated classification and consolidation of sequences from Colombia, Ecuador, and Venezuela. Phylogenetic analyses revealed a broadly distributed major lineage (previously designated D) circulating across the three countries, together with ongoing diversification and repeated introductions of genotype III within Colombia. Four minor lineages were identified, designated D.2.1, D.2.2, D.3.1, and D.3.2. Notably, the diversification of these minor lineages was accompanied by multiple non-synonymous substitutions. In particular, the two lineages currently circulating in Colombia, D.2.1 and D.2.2, are distinguished by approximately 20 mutations; however, the functional implications of these substitutions for viral virulence, pathogenicity, or vector competence remain unknown. These findings support the need for sustained and targeted genomic surveillance to detect and monitor emerging dengue virus lineages, prioritize them for epidemiological follow-up, and inform geographically focused public-health strategies. Overall, this study highlights the value of a globalized nomenclature, which enables the integration of genomic data across countries, facilitates the identification of emerging lineages in the region, and supports molecular surveillance efforts aimed at assessing their potential impact on disease presentation and public health.